P106 Incidence and outcome of occult uterine sarcoma: a multi-centre, retrospective study of 18604 operations performed for presumed uterine leiomyoma. (1st November 2019) - Yorganci, A; Meydanli, MM; Kadioglu, N; Sahin, H; Kayikcioglu, F; Taskin, S; Atasoy, L; Akgul, MA; Kinay, T; Tapisiz, OL; Haberal, N; Evliyaoglu, O; et al.
Abstract : Introduction/Background: The objective of this retrospective, multi-centred study was to determine the incidence of occult uterine sarcoma in women operated for presumed uterine leiomyoma. Methodology: We reviewed all myomectomy and hysterectomy operations performed with a pre-operative diagnosis of uterine leiomyoma at four tertiary centres, from January 2013 until December 2017, in Ankara, Turkey. The medical records of occult uterine sarcoma patients were analyzed to determine prognostic factors for disease-free survival (DFS) and overall survival (OS). Results: A total 18604 women underwent hysterectomy or myomectomy during the study period. There were 56 cases of occult uterine sarcomas (51 uterine leiomyosarcomas, and five endometrial stromal sarcomas). The incidence of occult uterine sarcoma was 0.30% (56/18604) or approximately 1/332. The median DFS was 31.0 months (95% confidence interval [CI] 9.6–52.3 months). The 3-year and 5-year DFS rates were 44.1% and 34.0%, respectively. The 3-year and 5-year OS rates were 68.8% and 50.0%, respectively. For 5-year DFS, stage of the disease (stage IA vs. more advanced stages; p=0.007), rapidly growing myoma (p=0.01) and complete surgical staging at initial operation (p=0.02) were found to be statistically significant in univariate analysis. However, only stage of the disease (Hazard Ratio: 3.45, 95% Confidence Interval 1.13–10.49; p=0.02) remained as an independent prognostic factor for decreased DFS in multivariate analysis. Conclusion: Our results indicated that the incidence of occult uterine sarcoma was 0.3% (1/332) in women operated for presumed uterine leiomyoma. Early and complete surgical resection might offer better DFS for these patients. Disclosure: Nothing to disclose.